Population Pharmacokinetic Model of Sublingual Buprenorphine in Neonatal Abstinence Syndrome. Issue 7 (14th July 2015) - Ng, Chee M.; Dombrowsky, Erin; Lin, Hopi; Erlich, Michelle E.; Moody, David E.; Barrett, Jeffrey S.; Kraft, Walter K.
<x xml:space="preserve">Abstract</x> Objective Neonatal abstinence syndrome (NAS)—a clinical entity of infants from in utero exposure to psychoactive xenobiotic and buprenorphine—has been successfully used to treat NAS. However, nothing is known about the pharmacokinetics (PK) of buprenorphine in neonates with NAS. To our knowledge, this is the first study to investigate the population pharmacokinetic of sublingual buprenorphine in neonates with NAS. Design A retrospective population PK analysis of: (1) neonates with NAS treated with sublingual buprenorphine in randomized, double blinded clinical study and (2) data from healthy adults from a previously published pharmacokinetic study. Setting Neonatal intensive care unit and general clinical research unit. Patients Twenty‐four neonates with NAS and five healthy adults. Interventions All participants received sublingual buprenorphine per study protocol. Measurements and Main Results A total of 303 PK data from 29 neonates and adults were used for model development. A population pharmacokinetic analysis was conducted using a first order conditional estimation with interaction in the NONMEM software program. A two‐compartment linear PK model with first‐order absorption process best described the pharmacokinetics of sublingual buprenorphine in neonates. The apparent clearance (CL) of buprenorphine was linearly related to body weight and matured with increasing age via two distinct saturated pathways. A typical neonate with NAS (body weight, 2.9 kg; postnatal age; 5.4 days) had a CL of 3.5 L/kg/hour and elimination half‐life of 11 hours. Phenobarbital did not affect the clearance of buprenorphine compared to neonates of similar age and weight. Conclusions This is the first study to investigate the population PK of sublingual buprenorphine in neonatal NAS. To our knowledge, this is also the first report to describe the age‐dependent changes of buprenorphine PK in this patient population. No buprenorphine dose adjustment is needed for neonates with NAS treated with buprenorphine and concurrent phenobarbital.